Sport and technology. An actor-network theory perspective - Kerr, R. (Manchester University Press, 2016)
1 What is technology? 2 Enhancement: which technologies are improved, and how? 3 The integration of `foreign` technologies into sporting practice 4 The actor-network of doping 5 The integration of science and medicine into sports training 6 Technologies for judging, umpiring and refereeing 7 Translating performances: the production of sports media broadcasts Conclusion References Index